Paleocanais no megaleque do rio Taquari: mapeamento e significado geomorfológico - Zani, Hiran; Assine, Mario Luis [UNESP] (Sociedade Brasileira de Geologia, 2011)
This paper presents the results of the frst systematic mapping of the paleochannel network on the Taquari megafan (Pantanal, Brazil). We used remote sensing data collected by the ASTER sensor, which captures images with 15 m square pixels. A total of 34 scenes, acquired from 2001 - 2006, were used in the analysis. These data were processed using a decorrelation stretch technique in order to obtain a better visual identifcation of the paleochannels. The mapping procedure began with the overlay of a 1:50.000 IBGE articulation, in order to systematize the extraction of features and to reduce the subjectivity inherent to visual analysis methods. We mapped a total of 33,205 km of paleochannels. The density of these features is related to the relative ages of distinct geomorphological compartments, known as depositional lobes. The mapped features preserve avulsion events that occurred on the megafan. The results suggest that low-magnitude avulsions occur more frequently than larger events.

Este trabalho tem como objetivo apresentar o primeiro mapeamento sistemático da rede de paleocanais existente no megaleque do Taquari. Foram utilizados dados de sensoriamento coletados pelo sensor ASTER, que produz imagens com pixel de 15 x 15 m. Foram necessárias um total de 34 cenas, adquiridas entre os anos de 2001 a 2006. Estes dados foram processados através da técnica de realce por decorrelação, visando melhor identifcação visual dos paleocanais. A etapa de mapeamento se iniciou com a sobreposição de uma quadrícula compatível com a articulação 1:50.000 do IBGE, a fm de sistematizar a extração das feições de interesse e diminuir a subjetividade inerente ao método de análise visual. Foram cartografados um total de 33.205 km de paleocanais. A densidade destas feições se mostrou relacionada com as idades relativas dos compartimentos geomorfológicos. As feições mapeadas preservam eventos de avulsão que ocorreram no megaleque, sugerindo que os de menor magnitude são mais frequentes.
Paleochannels on Taquari river megafan, Pantanal, Brazil: their mapping and geomorphological meaning
Keywords: avulsion; Pantanal wetland; remote sensing; ﬂuvial geomorphology; avulsão; Pantanal; sensoriamento remoto; geomorfologia ﬂuvial